Management education : fragments of an emancipatory theory - Klikauer, Thomas, 1962- (Palgrave Macmillan, 2017)
Written in the tradition of the Frankfurt School of critical theory, this book develops a practical theory designed to humanise management education. Inevitably encountering deeply authoritarian business schools, the author sets the rigidity of curriculum against a student-centred approach found in Honneth's concept of recognition and the Habermasian concept of communicative action. Management Education outlines measures for preventing Managerialism from colonising learning spaces that would prevent the practice of emancipatory learning from flourishing. The aim of the book is to allow students and teachers of business schools to create learning inside an education system based on humanity.
Keywords: Management -- Study and teaching.; Employee empowerment.; Industrial management -- Employee participation.; elektronické knihy; electronic books